The stabilization value of groundwater: evidence from Indian tank irrigation systems - Kuppannan, Palanisami; Giordano, Mark; Kakumanu, Krishna Reddy; Ranganathan, C.R. (Springer, 2012)
Groundwater is now a major source of agricultural water supply in many parts of the world. The value of groundwater as a new source of supply is well known. However, its additional buffering or stabilization value is less appreciated and even less analysed. Knowledge on groundwater?s stabilization value is advanced by developing and estimating an empirical model using the case of tank irrigation systems in Tamil Nadu, India. Unlike previous work, the model uses cross-sectional rather than time-series data. The results show that for the case-study region, the stabilization function added approximately 15% to supply value. Scenarios with surface water and electricity price were incorporated in the model. Increased surface-water supply and electricity price caused reduction in groundwater use but the percent of stabilization value of groundwater increased. The findings are used both to suggest improvements in tank irrigation systems and to further contextualize knowledge of groundwater?s stabilization value.